The Social Value of Can Batlló: Urban Regeneration Through New Administrative Tools in Barcelona - Mosquera Suárez, Jorge (Sens public, 2024)
The constant dialogue between social movements and local government has made the city of Barcelona a reference laboratory for urban regeneration and social innovation. However, in the past, the plurality of spaces managed by civil society did not correspond to clear co-management schemes and only recently a regulatory framework based on the concept of commons has been created: the Citizens Assets Programme. Within this new programme, the urban planning concession of the Can Batlló neighbours’ association–a self-managed community active since 2011 at the former industrial site–represents a further innovation. For the first time, an urban planning concession was granted to a self-managed non-profit entity–which considers that the community project of Can Batlló constitutes an important social benefit for the city of Barcelona–which measures and monitors it according to new administrative tools: the community balance, to track the social impact of the community; and the social return to valorise economically the voluntary work of the community in recovering the common and that “justifies” the investment made by the municipality in conceding the space. This research reconstructs the co-production of these new tools in order to study the effects and opportunities that they create both inside and outside the city of Barcelona, with particular attention to the economic valorisation of voluntary work as a means of communicating, attracting resources and legitimizing the work of self-managed communities within regenerated spaces.